The Mediation of Circulating Inflammatory Proteins in the Causal Pathway from Immune Cells to COPD - Yan K; Wang Y; Xin P (International Journal of COPD)
Kunrong Yan, Yingjian Wang, Peng Xin Department of Anaesthesia, Chaoyang Second Hospital, Chaoyang, Liaoning, People’s Republic of ChinaCorrespondence: Peng Xin, Email cy08xp@163.comObjective: Observational studies have indicated that immune cells and circulating inflammatory proteins may play a dual role in the progression of COPD; however, the precise mechanisms remain uncertain. The objective of this study was to ascertain the causal relationship between immune cells and COPD and to quantify the potential role of circulating inflammatory proteins as mediators.Methods: A two-sample Mendelian randomisation analysis was conducted involving 731 immune cells, 91 inflammatory proteins and COPD, utilising summary-level data from genome-wide association studies. The causal relationships between immune cells, inflammatory proteins and COPD were sequentially analysed by multivariate Mendelian randomisation and validated using Bayesian weighted Mendelian randomisation. Subsequently, sensitivity analyses were conducted, employing Cochran’s Q test to assess heterogeneity, MR-PRESSO and MR-Egger tests to assess pleiotropy, and reverse MR and Steiger directionality tests to rule out reverse causality. Lastly, a two-step approach was employed to ascertain the proportion of inflammatory proteins that mediate immune cell-mediated effects in COPD.Results: The combination of the inverse variance weighting method and the Bayesian weighting algorithm identified 30 immune cells that were found to be causally associated with COPD, as well as eight inflammatory proteins that were associated with COPD. By two-step analysis, six inflammatory proteins were found to mediate the effects of eight immune cell phenotypes on COPD, with CXCL10 having the highest percentage of mediation at 14.49%, followed by IL20RA at 11.47%.Conclusion: This study provides a comprehensive investigation of the causal relationship between immune cells and COPD, as well as an estimation of the proportion of the effect of inflammatory proteins as mediators. These findings facilitate the identification of individuals at high risk of COPD and offer novel insights for early prevention and clinical intervention.Keywords: Mendelian randomization, Bayesian weighted Mendelian randomization, immune cells, circulating inflammatory proteins, COPD, mediation analysis